Ortner’s Syndrome: Aortic Aneurysm as a Cause of Unilateral Vocal Cord Paralysis - Dayang Corieza Febriany; Cindy Chin; Mohamed Arif Hameed Sultan; Anand Raj Thangavelu (Penerbit UMS, 2023)
Hoarseness is a symptom of Ortner’s syndrome, a rare disorder caused by mechanical left recurrent laryngeal nerve compression by enlarged cardiovascular structures. This is a case of Ortner’s syndrome in an elderly 74-year-old male with an aortic arch aneurysm presenting with hoarseness. We believe the aneurysm causes the left recurrent laryngeal nerve compression, resulting in unilateral vocal cord paralysis. We emphasise the significance of Ortner’s syndrome as hoarseness of voice, a significant differential diagnosis in an elderly patient despite the absence of cardiac symptoms.